(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the effects of tax planning strategies on the firm value of listed manufacturing firms in Nigeria: an empirical analysis. Tax planning is a significant aspect of business strategy and a crucial exercise for effective and efficient financial planning activity which requires attention from managers of all functional areas in the firm. This study is guided by two specific objectives which include: to examine the effect of tax planning strategies on firm value of listed manufacturing firms in Nigeria and to evaluate the effect of effective tax rate on the firm value of listed manufacturing firms in Nigeria. Relevant literatures were reviewed including conceptual, theoretical and empirical literatures. Ex post facto research design was adopted. Secondary data from the audited financial statement of the listed manufacturing firms on Nigerian Exchange Group were collected. Descriptive and inferential statistics were used to analyse the data. In conclusion the result of the regression shows that tax planning strategies have demonstrated to have an insignificant relationship with farm value of listed manufacturing firms in Nigeria. Income tax rate and effective marginal tax rate have negative relationship with firm value while effective tax rate has positive relationship with firm value. The study recommends that both people and corporations be encouraged to proactively adopt a thorough tax planning policy. Taxpayers might find chances to maximize credits, deductions, and tax-exempt investments by knowing the newest tax rules and consulting a knowledgeable tax professional.